A importância da leitura reflexiva permanente para o profissional docente - SANTOS, Neurilene Ribeiro dos (2022)
The use of reading for the professional is a very important instrument for their own learning. In this context, the present study expressed a study about the importance of the permanent reading for the teaching professional. For this, this research aimed to analyze a bibliographical approach. The literature review showed that reading should always be part of the daily life of the human being, especially the teacher, which facilitates the students' understanding of the importance of reading, and the teacher should be a favorable point for learning. The discussion has shown that reading contributes to the development and ability of being critical of one's own opinions and reading the world. Therefore, it is considered that the daily reading of the teacher is of great relevance for the teaching-learning process of the students and the professional itself. The conclusion expresses that the reading of the teacher is in fact a very important channel for the exercise of the teacher in the school environment, in order to provide a more consistent learning both for the students and Teacher.